Gas–liquid mass transfer and bubble size distribution in a multi‐Cyclone separator. Issue 1 (18th October 2018) - Xu, Xiao; Lu, Hao; Qian, Yundong; Zhang, Bohan; Wang, Hualin; Liu, Honglai; Yang, Qiang
Abstract : This article discusses the use of a multi‐cyclone separator, which is a simplified form of a degassing hydrocyclone, in the separation of sweeping nitrogen bubbles and dissolved oxygen from water. The motion of the nitrogen bubbles and mass transfer of dissolved oxygen is discussed. It was observed that the Sauter mean diameter and gas volume in the swirling flow region as well as the total gas holdup increased as the volumetric ratio of gas to liquid flow increased. Almost all bubbles were found to exit through the gas outlet, indicating optimum performance of the bubble‐separation process. The multi‐cyclone separator was found to achieve good performance for the mass transfer of oxygen from water to nitrogen. This work is important in predicting the destination of bubbles and dissolved gas in swirling flow. © 2018 American Institute of Chemical Engineers AIChE J, 65: 215–223, 2019